2007
DOI: 10.1002/app.27210
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical properties of a poly(ϵ‐caprolactone)/graphite oxide composite

Abstract: The effect of graphite oxide (GO) as the enforcing filler on the properties of poly(e-caprolactone) (PCL) was investigated in this study. Through the introduction of GO, the Young's modulus of PCL was increased from 340 to 1000 MPa, and the tensile strength of PCL was increased from 15 to 26 MPa. Furthermore, the interlayer distance of GO (0.6 nm) was found to expand to 1.1 nm in the PCL/GO composite, which indicated the intercalation of the PCL chain into the GO layers. Because of this intercalation structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(94 citation statements)
references
References 30 publications
3
86
0
2
Order By: Relevance
“…Previous work on graphene oxide [20,21] had introduced a mixing method for the production of graphene oxide polymer materials. Adapting this method using highly reduced, well dispersed graphene resulted in graphene/polycaprolactone composites with good mechanical and conducting properties but poor graphene dispersion in the matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work on graphene oxide [20,21] had introduced a mixing method for the production of graphene oxide polymer materials. Adapting this method using highly reduced, well dispersed graphene resulted in graphene/polycaprolactone composites with good mechanical and conducting properties but poor graphene dispersion in the matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Graphene oxide was synthesized from natural graphite powder using a modified Hummers' method in two steps using K 2 S 2 O 8 , P 2 O 5 and H 2 SO 4 followed by H 2 SO 4 , KMnO 4 and H 2 O 2 to achieve better oxidation of graphite (20,21).…”
Section: Preparation Of Graphene Oxide (Go)mentioning
confidence: 99%
“…From these values, it is observed that the conductivity increases by 2 orders with increasing wt.% ratio of PVA/PVP : GO (0.1, 0.2, and 0.3). From the figure, it is clear that as the temperature increases, the conductivity increases predominantly [37].…”
Section: Conductivity Studiesmentioning
confidence: 95%
“…9 Recently, polymer/graphite nanosheet composites have been intensively studied because of their excellent properties. [10][11][12][13] The weak interplanar forces allow for certain atoms, molecules, and ions to intercalate into the interplanar spaces of the graphite. 9 However, unlike the layered clay, there are no reactive ionic groups on the surface of the original layered graphite.…”
Section: Introductionmentioning
confidence: 99%